2014
DOI: 10.1371/journal.pone.0101107
|View full text |Cite
|
Sign up to set email alerts
|

FLIC: High-Throughput, Continuous Analysis of Feeding Behaviors in Drosophila

Abstract: We present a complete hardware and software system for collecting and quantifying continuous measures of feeding behaviors in the fruit fly, Drosophila melanogaster. The FLIC (Fly Liquid-Food Interaction Counter) detects analog electronic signals as brief as 50 µs that occur when a fly makes physical contact with liquid food. Signal characteristics effectively distinguish between different types of behaviors, such as feeding and tasting events. The FLIC system performs as well or better than popular methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
212
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(215 citation statements)
references
References 20 publications
(24 reference statements)
3
212
0
Order By: Relevance
“…Within a few years, electron microscopy is likely to produce images of an entire fly brain that can be used for circuit tracing. New feeding assays allow a more realtime picture of the subtleties of feeding behavior (Itskov et al 2014, Ro et al 2014, Qi et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Within a few years, electron microscopy is likely to produce images of an entire fly brain that can be used for circuit tracing. New feeding assays allow a more realtime picture of the subtleties of feeding behavior (Itskov et al 2014, Ro et al 2014, Qi et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila central nervous system (CNS) executes food intake control using various mechanisms, which can be studied using a wide range of methods. Food labeling by dyes or radioactivity, food uptake quantification by the so-called capillary feeder assay , proboscis extension reflex assay (Shiraiwa and Carlson, 2007), and automated food intake monitoring using the flyPAD or Fly Liquid-Food Interaction Counter (Ro et al, 2014) can be used to quantify feeding. Food preference assays are used to determine important feeding parameters such as total intake, meal size, meal frequency and feeding motivation (reviewed in Branch and Shen, 2017;Deshpande et al, 2014).…”
Section: Musclementioning
confidence: 99%
“…2D). Third, we used a novel assay [the fly liquid food interaction counter (FLIC)] that quantifies food interactions by allowing the fly to complete a low-voltage electrical circuit by touching or consuming a liquid food while standing on a metal base (18). We found that there was no difference between the ΔGr64 and control flies in the amount of time spent interacting with the food (P = 0.56; Fig.…”
Section: Significancementioning
confidence: 99%